Consumer willingness to pay a premium for orange-fleshed sweet potato puree products: a gender-responsive evidence from Becker–DeGroot–Marschak experimental auction among low- and middle-income consumers in selected regions of Nairobi, Kenya - Wangithi, C.M.; Nyangaresi, A.M.; Srinivasulu, R.; Moyo, M.; Muzhingi, T.; Kawarazuka, Nozomi (Frontiers Media, 2023)
Vitamin A deficiency (VAD) is a major public health problem affecting people of all ages, particularly women of reproductive age and young children in the Global South. Nutrient-enriched (biofortified) orange-fleshed sweet potato (OFSP) has promising potential as a sustainable food vehicle to combat VAD. Part of ongoing efforts to combat VAD, particularly among the urban poor populations, include the introduction of innovative OFSP puree, which is utilized as a functional and substitute ingredient in widely consumed baked and fried products. In Kenya, the OFSP puree is used to make commercial products that are affordable by low- and middle-income households. However, there is limited knowledge of consumer awareness, willingness to pay (WTP), and/or how gender plays a role in the uptake of these products. Following a multistage sampling technique, this study employs the Becker–DeGroot–Marschak (BDM) experimental auction method to assess if men and women consumers—from selected, highly populated low- and middle-income areas of Nairobi County in Kenya—are aware and if they would be willing to pay for OFSP puree products. Integrating gender considerations, we use three of the most widely consumed OFSP puree products, bread, buns, and chapati, and three treatment categories, naive, nutritional information, and OFSP puree substitute products' references prices to deduce the WTP for OFSP puree products among men and women. Results showed limited awareness of OFSP and OFSP puree products among men and women. However, both men and women were willing to pay a premium for the OFSP puree products. The intergender comparison showed that women were more willing to pay a premium for the OFSP puree products than men. Gender, age, education, knowledge of OFSP puree products, income category, availability of nutritional information, and reference pricing stand out as significant determinants of WTP.